Foreign language for specific purposes: methodological aspects of teaching - Poliakova, Tetiana; Samarina, Viktoriia (My University, 2022)
Teaching a technical language is becoming increasingly important in modern European society which is characterized by movements of various kinds. Besides, groups of students are becoming more differentiated, and teachers who are not usually experts in a particular field face difficulties when creating courses for students as opportunities for training and advanced training for teachers are limited. There are a lot of problems that remain open or partially analyzed, and there isn’t just one way to solve them. But nevertheless we would like to try to present some solutions to these problematic issues and show how and with which linguistic means and instruments specialized languages can be described and what impact this can have on teaching.

Викладання технічної мови стає дедалі актуальнішим у сучасному європейському суспільстві, що характеризується різними «рухами», проте групи студентів стають більш диференційованими, а викладачі, які зазвичай не є експертами в певній галузі, зазнають труднощів зі створенням курсів для студентів, оскільки можливості для навчання чи підвищення кваліфікації трапляються не часто. Є багато питань, які залишаються відкритими або частково розкритими, і єдина відповідь на них не завжди можлива, однак все одно варто спробувати представити вирішення таких проблемних питань. Необхідно показати, як саме та за допомогою яких засобівта інструментів можна описати спеціалізовані мови, а також те, який вплив це може чинити на викладання.
Іноземна мова професійного спрямування: методичні аспекти викладання
Keywords: technical language; languages for specific purposes; LSP research; LSP teaching; corpora; технічна мова; мова для спеціальних цілей; дослідження мови для спеціальних цілей; викладання мови для спеціальних цілей; корпуси